Ant-ic actions. (1st July 2015) - MacDonald, Fiona
These Artist Pages describe the process of, and the ethical problems raised by my creative interaction with wood ants (Formica rufa) in a Kent forest (England) in 2014. I draw on Haraway, Massumi, Baker and Jevbratt to touch on questions around collaboration, rules, knowing and responsibility.